Relationship between COVID-19 information sources and attitudes in battling the pandemic among the Malaysian public: cross-sectional survey study - Mohamad, Emma; Tham, Jen Sern; Ayub, Suffian Hadi; Hamzah, Mohammad Rezal; Hashim, Hasrul; Azlan, Arina Anis (JMIR Publications, 2020)
Background: There are multiple media platforms and various resources available for information on COVID-19. Identifying people’s preferences is key to building public confidence and planning for successful national health intervention strategies.